Moderating role of trust in the relationship between corporate governance and performance of agricultural cooperatives in Nigeria - Mohammed Umar, Ibrahim; Mustafa, Hasri; Sidek, Shafie; Lau, Wai Yeng (Elsevier, 2024)
This study aims to identify the moderating construct of trust in the performance of agricultural cooperatives in North-Western Nigeria. Business management cannot be overseen by the owner alone; it may require the services of other professionals. However, the high incidence of corrupt practices in the public and private sectors in developing African countries cripples many businesses. It makes it difficult to entrust the management of organisations to a third party. Trust is essential, especially in an environment with a loose execution of legal charges. Although a direct relationship between corporate governance and performance has been established across many disciplines, the influence of trust as an interactive construct has yet to be established. Therefore, this study addresses this gap. This study used concurrent triangulation design with a significant quantitative approach complemented by the qualitative segment involving seven open-ended questions. Data were collected from 384 cooperative for rice farmer’s by used of a survey design. Structural Equation Modelling was used to assess the measurement model to test the hypotheses. An Excel spreadsheet was used to pre-code the data derived from open-ended questions, and later exported to ATLAS.ti software for qualitative analysis through coding, group coding and network. The findings revealed that corporate governance and trust significantly influenced agricultural cooperative performance. The moderating effect of trust on corporate governance was supported. The findings illustrate how social capital theory explains the processes of African trust, especially in corrupt environments with weak legal penalties. This study examines corporate governance within the internal control mechanisms of an agricultural cooperative society. Further studies should understand corporate governance within an external tie. To our knowledge this is the first study to examine the moderating effect of trust on the interacting variables in the African social capital theory model.